Development of non-destructive testing (NDT) technique for HIPed interface by Compton scattering X-ray spectroscopy. (June 2022) - Sakurai, Hiroshi; Suzuki, Kosuke; Ishii, Shoya; Hoshi, Kazushi; Nozawa, Takashi; Ozaki, Hidetsugu; Haga, Hiroto; Tanigawa, Hiroyasu; Someya, Yoji; Tsuchiya, Masao; Takeuchi, Hiroshi; Tsuji, Naruki
Highlight: HIPed interface of F82H steel was analyzed using high energy X-rays (115.56 keV). The analysis revealed the presence of SiO x and TaO x at the HIP interface and W accumulation near the HIP interface. The high energy X-ray spectra can be a non-destructive testing (NDT) technique for a HIPed interface of F82H steel. Abstract: High energy X-rays (115.56 keV) were used to measure the HIPed interface of F82H steel. The X-ray energy spectra of the samples were analyzed focusing on W and Ta fluorescence X-rays, Compton scattering and elastic scattering X-rays. The results suggest the presence of SiO x and TaO x at the HIP interface and the accumulation of W near the HIP interface. These results indicate that high-energy X-ray spectrum analysis can be a non-destructive testing technique (NDT) to evaluate precipitates at the HIP interface of F82H steel.